Does joining global accounting firm networks and associations affect audit quality and audit pricing? Evidence from China. Issue 6 (10th November 2021) - Li, Wei; Liu, Huilong; Wang, Xizi
Abstract : This study investigates the impact of accounting firms joining global accounting firm networks and associations (AF N&As) on audit quality and audit pricing in China. We find that after their accounting firms join global AF N&As, client firms' accrual-based earnings management is reduced. However, we find no evidence that audit fees are significantly affected. Cross-sectional analysis suggests that improvements in audit quality resulting from accounting firms joining global AF N&As are more pronounced when auditors have less audit experience, clients have more subsidiaries or auditor tenure is shorter. Additional tests suggest that joining AF N&As reduces the likelihood of accounting firms being dismissed by clients and increases the market share of the accounting firms.